HUBUNGAN KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI UNIT RAWAT JALAN RSI IBNU SINA PADANG - Fitriyati; Hayulita, Sri; Desri, Nentien; Avis, Mairinal (Jurnal Kesehatan Lentera 'Aisyiyah, 2024)
The quality of healthcare services reflects the alignment between the services provided and patient satisfaction. Health insurance, such as BPJS, is essential for providing health protection and fulfilling basic health needs. Patient satisfaction is a key indicator in measuring the quality of services, which is heavily influenced by service performance. If the service performance meets or exceeds patient expectations, satisfaction will be achieved. This study aims to analyze the relationship between the quality of healthcare services and patient satisfaction with BPJS in the outpatient unit of RSI Ibnu Sina Padang in 2024. The research method used is descriptive analytic with a cross-sectional approach, with the population consisting of outpatient patients and a sample of 70 respondents selected through purposive sampling. The independent variable is the quality of BPJS healthcare services, and the dependent variable is patient satisfaction. Spearman Rank test was used for data analysis with a significance level of p ≤ 0.05. The results show a p value of 0.012, indicating a significant relationship between the quality of healthcare services and patient satisfaction. Therefore, it is expected that the hospital will improve service and employee performance to increase patient satisfaction with the services provided.